2013
DOI: 10.1093/mnrasl/slt050
|View full text |Cite
|
Sign up to set email alerts
|

Spectropolarimetry of the Type Ia supernova 2012fr

Abstract: Spectropolarimetry provides the means to probe the 3D geometries of Supernovae at early times. We report spectropolarimetric observations of the Type Ia Supernova 2012fr at four epochs: -11, -5, +2 and +24 days, with respect to B-lightcurve maximum. SN 2012fr is a normal Type Ia SN, similar to SNe 1990N, 2000cx and 2005hj (that all exhibit low velocity decline rates for the principal Si II line). The SN displays high velocity components at -11 days that are highly polarized. The polarization of these features… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 28 publications
(30 reference statements)
6
69
0
Order By: Relevance
“…(2) The nickel is concentrated in the center, while we are interested in the outer layers that are first to interact with the ISM. (3) The observed very low level continuum polarization at the first few weeks in SN 2012fr points to a symmetrical explosion that is inconsistent with the merger-induced explosion scenario (Maund et al 2013). Namely, it seems that explosion is not far from spherical from the beginning.…”
Section: A Low-mass Helium Wdmentioning
confidence: 92%
“…(2) The nickel is concentrated in the center, while we are interested in the outer layers that are first to interact with the ISM. (3) The observed very low level continuum polarization at the first few weeks in SN 2012fr points to a symmetrical explosion that is inconsistent with the merger-induced explosion scenario (Maund et al 2013). Namely, it seems that explosion is not far from spherical from the beginning.…”
Section: A Low-mass Helium Wdmentioning
confidence: 92%
“…To the best of our knowledge this includes only SN 1986G (NGC 5128; Cen A), 2006X (NGC 4321;M100), 2008fp (ESO 428-G14), and the recent 2014J (NGC 3034; M 82). Other Type Ia SN have spectropolarimetric data: 1997dt, 2002bf, 2003du, 2004dt (Leonard et al 2005; 2001el (Wang et al 2003);2007sr (Zelaya et al 20132005ke (Patat et al 2012; 2011fe (Smith et al 2012); 2012fr (Maund et al 2013); however, the low reddening associated with these events makes the study of the interstellar polarization (ISP) wavelength dependence very uncertain, if not impossible (see also Zelaya et al, in prep. ).…”
Section: Datamentioning
confidence: 99%
“…A Pearson coefficient r calculated including all the points is reported. After being properly converted (see the text), spectropolarimetric data of normal SNe Ia (Wang et al 2007;Maund et al 2013) are also plotted for comparison (purple diamonds). Purple error bars mark the averaged uncertainties for these values.…”
Section: Degree Of Polarisation and Light Curve Propertiesmentioning
confidence: 99%
“…However, violent merger models have been called into question -particularly for normal SNe Ia -because they produce highly asymmetric ejecta that appear to be in contrast with the low level of polarisation typically observed (see Wang & Wheeler 2008, for a review). For instance, Maund et al (2013) recently obtained high-quality data for SN 2012fr at four different epochs and found that the polarisation was consistently below 0.1 per cent. They suggested that such low level of polarisation was inconsistent with the asymmetric 56 Ni distribution predicted by the violent merger model of Pakmor et al (2012).…”
Section: Introductionmentioning
confidence: 99%